Stochastic Models of Crude Oil Prices and Their Applications on Option Pricing - Cao, Hang (2015)
For decades, geometric Brownian motion has proved a great success in describing the price process, because it catches the stochastic character of the price process. However, when it comes to commodity prices, there are several additional features. Mean reverting and jump diffusion phenomenon is two characters among them have been researched most in the past decades.